Distributed Leadership Collaboration Factors to Support Idea Generation in Computer-Supported Collaborative e-Learning - Lambropoulos, Niki; Bakharia, Aneesha; Gourdin, Alain (Human Technology, 2011)
This paper aims to identify, discuss and analyze students’ collaboration factors related to distributed leadership (DL), which correlates with interaction quality evident in idea generation. Scripting computer-supported collaborative e-learning (CSCeL) activities based on DL can scaffold students’ interactions that support collaboration and promote idea generation. Furthermore, the associated tools can facilitate collaboration via scripting and shed light on students’ interactions and dialogical sequences. Such detailed planning can result in effective short e-courses. In this case study, 21 MSc students’ teams worked on a DL project within a 2-day e-course at the IT Institute (ITIN), France. The research methods involved a self-reported questionnaire; the Non-Negative Matrix Factorization (NNMF) algorithm with qualitative analysis; and outcomes from the Social Network Analysis (SNA) tools implemented within the forums. The results indicated that scripting DL based on the identified distributed leadership attributes can support values such as collaboration and can be useful in supporting idea generation in short e-courses.